2009
DOI: 10.1111/j.1750-3841.2009.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitroAntilisterial Effects of Citrus Oil Fractions in Combination with Organic Acids

Abstract: The objectives of this study were to screen activity of citrus essential oil fractions (EOs) alone and in combination with organic acids against 2 species of Listeria. Five citrus EOs were initially screened by disc diffusion assay for antibacterial activity. Cold pressed terpeneless Valencia orange oil (CP terpeneless oil) had the strongest bacteriostatic (MIC) and bactericidal (MBC) properties at 0.55% and 1.67%, respectively. Four organic acids were tested for effectiveness against Listeria. Citric and mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 45 publications
1
53
1
2
Order By: Relevance
“…Synergism among antilisterial agents have been investigated to achieve higher levels of food safety standards (Kim et al 2008;Friedly et al 2009); but no report has been found or published in the literature on the synergistic effect of enterocin A and thyme EOs against L. monocytogenes . The exact mechanism of action of the essential oil and bacteriocins is not known, but some authors hypothesized that these components cause disruption of the cell membrane (Hyldgaard et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Synergism among antilisterial agents have been investigated to achieve higher levels of food safety standards (Kim et al 2008;Friedly et al 2009); but no report has been found or published in the literature on the synergistic effect of enterocin A and thyme EOs against L. monocytogenes . The exact mechanism of action of the essential oil and bacteriocins is not known, but some authors hypothesized that these components cause disruption of the cell membrane (Hyldgaard et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The concept of combining EOs and OAs has proven to be efficacious as an alternative to Antimicrobial Growth Promoters (AGP) in animal nutrition (Aksit, Goksoy, Kok, Ozdemir, & Ozdogan, 2006). Moreover, it has been reported that there was a significant synergistic antibacterial effect by combination of citrus oils and OAs against L. monocytogenes (Friedly et al, 2009). In previous experiments (Tawema, Han, Salmieri, Vu, & Lacroix, 2014), we developed two natural antimicrobial formulations which composed of lemongrass EO (for Asian formulation) or oregano EO (for Mediterranean formulation) plus citrus extract and lactic acid.…”
Section: Introductionmentioning
confidence: 99%
“…and Clostridium sp., Staphylococcus aureus), spoiling microorganisms (Lactobacillus sp. in juices), yeasts and molds (Saccharomyces cerevisiae, Aspergillus parasiticus, Aspergillus flavus, Alicyclobacillus acidoterrestris, Fusarium oxysporum) (Fisher & Phillips, 2008;Friedly et al, 2009;Bevilacqua, Campaniello, Sinigaglia, Ciccarone, & Corbo, 2012. Citral and carvacrol were used at different concentrations for controlling the growth of E. coli K12 and Listeria innocua at different temperature (Belda-Galbis, Pina-P erez, Leufv en, Martínez, & Rodrigo, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Study has showed a synergistic effect, against Listeria species, with the combination of terpenic fractions of citrus oil and organic acids as malic acid and ascorbic acid (FRIEDLY et al, 2009). The copaiba oil, which is composed by a sesquiterpenic and terpenic fractions, may has a similar action in combination with organic acids.…”
Section: Resultsmentioning
confidence: 99%